Penggunaan Tepung Cacing Tanah (Lumbricus rubellus) sebagai Aditif Pakan terhadap Penampilan Produksi Ayam Pedaging, Profil Darah dan Kecernaan Protein (The Effect of Earthworm (Lumbricus rubellus) Meal as Feed Additive on Broiler Production Performance, - Hardi Julendra; Zuprizal (Zuprizal); Supadmo (Supadmo) (Buletin Peternakan, 2010)
The objective of this research was to study the use of earthworm meal (Lumbricus rubellus) (TCT) as feed additive on broiler performance, blood profile and protein digestibility. The experiment used 100 day old chicken of cobb strain (CP 707), for 35 days feeding trial. The birds were randomly divided into four dietary treatments (R0: without TCT addition, R1: 0.5% TCT addition, R2: 1% TCT addition, R3: 1.5% TCT addition) with five replications, wich consisted five chickens each. The experimental design used Completely Randomized Design (CRD) of one way ANOVA then continued with Duncan test. Performance test was conducted by recording body weight gain, feed consumption and feed efficiency. Blood profile test was obtained by counting the number of erythrocyte, leukocyte and lymphocytes, whereas protein digestibility test used the collection method of excreta and ileum content. The result showed that feed consumption of R1 (2,065 g), R2 (2,025.4 g), R3 (2,075.3 g) were significantly different (P<0.05) fromR0 (2,309.8 g), while the body weight gain were not different among treatments and FCR of R1 (1.78), R2 (1.78), R3 (1.78) were significantly different (P<0.05) from R0 (2.04). The result of blood profile test showed that the number oferythrocyte among treatments were not significantly different, the number of leukocyte of R1 (18,575 μl), R2 (18,200 μl), R3 (20,175 μl) were found significantly higher (P<0.05) than R0 (16,675 μl) and lymphocytes of R1 (22.7%), R2 (21.8%), R3 (23.6%) were significantly higher (P<0.05) than R0 (15.2%). Protein digestibility of R3 (91.69%) was significantly different (P<0.05) from R0 (81.75%), R1 (90.48%) and R2 (85.99%), while R1 (90.48%) was significantly different (P<0.05) from R0 (81.75%), but R2 (85.99%) was not significantly different from R0 (81.75%). It could be inferred that earthworm meal addition as feed additive could improved production performance of broiler, the poultry health through blood profile, and enhanced the protein digestibility.(Key words: Feed additive, Earthworm meal, Broiler)